THE ROLE OF THE INDONESIAN NATIONAL ARMED FORCES (TNI) IN ADDRESSING TERRORISM AS AN EFFORT TO SAFEGUARD THE SOVEREIGNTY AND INTEGRITY OF THE UNITARY STATE OF THE REPUBLIC OF INDONESIA - Casmudin; Sujono; Sudarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
Acts of terrorism carried out systematically and massively create an atmosphere of widespread terror for citizens, effectively and efficiently, that the involvement of the TNI in eradicating criminal acts of terrorism, which is part of acts of terrorism, is not in the realm of law enforcement. Therefore, it is interesting to examine the position of the Indonesian National Army in the National Defense System of the Republic of Indonesia and the role of the Indonesian National Army in dealing with acts of terrorism as an effort to maintain the sovereignty and integrity of the Unitary State of the Republic of Indonesia. To answer these problems, normative legal research methods (normative juridical) are used with a statutory approach, case approach, conceptual approach, using secondary data obtained from primary, secondary and tertiary legal material sources. The research found that the position of the Indonesian National Army in the National Defense System of the Republic of Indonesia and the Role of the Indonesian National Army in Handling Acts of Terrorism as an Effort to Maintain Sovereignty is regulated in Article 30 Paragraph (5) of the 1945 Constitution of the Republic of Indonesia, apart from that in Paragraph (2) and Paragraph (3) This is confirmed in Article 3 and Article 4 of Law 34/2004 or the TNI Law, which states that in the deployment and use of military force, the TNI is subordinate to the President. Then the role of the Indonesian National Army in handling acts of terrorism as an effort to maintain the sovereignty and integrity of the Unitary State of the Republic of Indonesia as intended in Article 5 jo. Article 7 Paragraph (2) letter b number 3 which relates to the main tasks of the TNI in military operations other than war gives the TNI the authority to deal with acts of terrorism, based on state policies and political decisions. The position of the TNI in the state administration system is the main component of the state defense system to protect sovereignty, territorial integrity and the safety of the nation. To provide legal certainty and justice, it needs to be strictly regulated in ministerial regulations and/or Commander-in-Chief regulations regarding the role and duties of the TNI in dealing with acts of terrorism.